1998
DOI: 10.1002/(sici)1097-0231(19981130)12:22<1715::aid-rcm397>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-flight secondary ion mass spectrometry of Fmoc-amino acids linked to solid supports through ionic interactions

Abstract: The TOF-SIMS (time-of-flight-secondary ion mass spectrometry) spectra of Fmoc-amino acids linked to solid supports through ionic interactions have been studied to examine if easy desorption of preformed ions from the surface occurred. Preliminary results indicated that the structure of the polymer affected the nature of the recovered ions. However, in the case of widely used polystyrene based supports, characteristic ions of the amino acids were clearly observed with noticeable abundances. Moreover, an analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…Using TOF-SIMS the presence of the Fmoc group on the surface of the samples was monitored by detection of secondary ions at m/z (mass/charge ratio) of 179 D. 14 Individual amino acids, and their associated surface coverage, were monitored by specific secondary ion peaks (associated with C 9 H 8 N + and C 14 H 11 + ) as reported in Fig. 2a for tryptophan (Trp).…”
Section: Resultsmentioning
confidence: 99%
“…Using TOF-SIMS the presence of the Fmoc group on the surface of the samples was monitored by detection of secondary ions at m/z (mass/charge ratio) of 179 D. 14 Individual amino acids, and their associated surface coverage, were monitored by specific secondary ion peaks (associated with C 9 H 8 N + and C 14 H 11 + ) as reported in Fig. 2a for tryptophan (Trp).…”
Section: Resultsmentioning
confidence: 99%
“…Both the isomers show (Table and also Supporting Information) an ion at m/z 157 ([M + H–Fmoc + H–CH 3 OH] + ). Besides, the former shows product ions at m/z 171 ([M + H–Fmoc + H–H 2 O] + ), 132 (y 1 + ) and 129 ([M + H–Fmoc + H–CH 3 OH–CO] + ) and the latter shows a low abundance ion at m/z 161 ([M + H‐Fmoc + H‐CO] + ) and an abundant ion at m/z 72 corresponding to the immonium ion (a 1 + ), a characteristic ion for the presence of valine at the N‐terminus. The formation of the y 1 + ion for 5 and the immonium ion (a 1 + ) for 7 is in agreement with higher proton affinity of valine compared to that of glycine .…”
Section: Resultsmentioning
confidence: 99%
“…Goel and Kenny also reported the mechanism for the formation of the b 1 ‐1 and corresponding a 1 ‐1 ions in the product ion mass spectra of N‐para ‐ferrocenylbenzoyl dipeptide esters. A literature survey revealed that there are very few reports on mass spectral studies of Fmoc protected peptides/amino acids . To examine the effect of the Fmoc‐ group on the fragmentation of the dipeptides, we have studied a series of Fmoc‐protected dipeptide positional isomers using both positive and negative ion ESI‐MS/MS.…”
mentioning
confidence: 99%
“…These ions are absent for 3 . Instead, the latter shows an abundant ion at m / z 120 corresponding to the immonium ion of phenylalanine21 (Scheme ), a characteristic ion for the ureidopeptides derived from phenylalanine at the N‐terminus. A low abundance ion is observed at m / z 104 corresponding to the loss of combination of PhCH 2 CN and CO.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the MS 3 CID of m / z 201 of 5 and 7 gives (Supporting Information) low abundance ion at m / z 158 (loss of HNCO). Besides, the former shows an abundant ion at m / z 172 by the loss of CH 2 = NH (Scheme ) and the latter gives abundant ions at m / z 90 (loss of (CH 3 ) 2 CHCH 2 CN and CO) and m / z 86 corresponding to the immonium ion of leucine21 (Scheme ). Thus, the MS 3 spectra of m / z 201 ion of 5 and 7 are also useful to distinguish between the ureidopeptides derived from glycine and leucine at the N‐terminus.…”
Section: Resultsmentioning
confidence: 99%